1998
DOI: 10.1086/314526
|View full text |Cite
|
Sign up to set email alerts
|

Pneumococci Stimulate the Production of the Inducible Nitric Oxide Synthase and Nitric Oxide by Murine Macrophages

Abstract: The role of nitric oxide (NO) in the pathophysiology of gram-positive sepsis is uncertain. In inflammatory conditions, high-output NO production is catalyzed by the enzyme inducible nitric oxide synthase (iNOS). The ability of 2 strains of pneumococci, pneumococcal cell wall preparations, and purified pneumococcal capsule (Pnu-Imune 23) to trigger the production of iNOS protein and NO in RAW 264.7 murine macrophages was tested. Live pneumococci, oxacillin-killed pneumococci, and pneumococcal cell wall preparat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 41 publications
5
30
1
Order By: Relevance
“…RAW 264.7 cells were stimulated with GBS, at concentrations of 10 6 and 10 7 cfu/mL, a low concentration of rIFN-␥ (10 U/mL), and either ampicillin, cefotaxime, rifampin, or clinda-420 mycin. Our preliminary experiments demonstrated no detectable iNOS protein accumulation by cells exposed to GBS and antibiotics in the absence of rIFN-␥ (not shown), consistent with our previous studies of iNOS up-regulation by other Gram-positive bacteria (18,(21)(22)(23). Stimulation of RAW 264.7 cells with GBS exposed to rifampin or clindamycin led to markedly less iNOS protein accumulation compared with the cefotaxime or ampicillin experimental groups (Fig.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…RAW 264.7 cells were stimulated with GBS, at concentrations of 10 6 and 10 7 cfu/mL, a low concentration of rIFN-␥ (10 U/mL), and either ampicillin, cefotaxime, rifampin, or clinda-420 mycin. Our preliminary experiments demonstrated no detectable iNOS protein accumulation by cells exposed to GBS and antibiotics in the absence of rIFN-␥ (not shown), consistent with our previous studies of iNOS up-regulation by other Gram-positive bacteria (18,(21)(22)(23). Stimulation of RAW 264.7 cells with GBS exposed to rifampin or clindamycin led to markedly less iNOS protein accumulation compared with the cefotaxime or ampicillin experimental groups (Fig.…”
Section: Resultssupporting
confidence: 90%
“…In the studies of iNOS protein accumulation, cells were also exposed to low concentrations of rIFN-␥, which was required for iNOS production in response to the GBS isolate. We have previously reported that co-incubation with low doses of rIFN-␥ was required for induction of iNOS protein accumulation in RAW 264.7 cells stimulated with either antibiotic-treated S. pneumoniae (18,21), lipoteichoic acid purified from viridans streptococci (12), or pyrogenic exotoxins A or C isolated from Streptococcus pyogenes (23).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, although ROS may of itself be dispensable as an antimicrobicidal, it can still contribute to pneumococcal killing through formation of RNS. Microbial components, including the toxin pneumolysin and pneumococcal cell wall, stimulate macrophage NO production and NO-mediated bacterial killing [66][67][68]. In keeping with this, we and others have shown that mice that lack NOS2 are less able to clear S. pneumoniae from the lung [33,69].…”
Section: Microbicidal Mechanisms By Which Macrophages Kill S Pneumoniaesupporting
confidence: 54%
“…Weinberg (30) has reviewed the reports from 1989 to 1998 regarding NO production and iNOS expression in human mononuclear phagocytes in which there were some difficulties in detecting NO production, partly depending on the method used. Rodent mononuclear phagocytes have been used for many in vitro studies (31,32), mainly because they are more sensitive.…”
Section: Discussionmentioning
confidence: 99%